2006
DOI: 10.1111/j.1572-0241.2006.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Gallbladder Stent Placement for Treatment of Symptomatic Cholelithiasis in Patients with End-Stage Liver Disease

Abstract: Endoscopic stenting of the gallbladder may be a potential treatment for symptomatic gallbladder disease in patients with cirrhosis awaiting liver transplantation, considered to be high-risk for cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 23 publications
1
62
0
Order By: Relevance
“…Several investigators have reported that ETGBD is effective and safe for patients with acute cholecystitis (6)(7)(8)17) and that EGBS is one of the promising alternative treatment options (9)(10)(11)(12)(13)(14)(15)(16)(17). In patients with concomitant unresectable cancer, it is important to control infectious diseases, including acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported that ETGBD is effective and safe for patients with acute cholecystitis (6)(7)(8)17) and that EGBS is one of the promising alternative treatment options (9)(10)(11)(12)(13)(14)(15)(16)(17). In patients with concomitant unresectable cancer, it is important to control infectious diseases, including acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…The goal for patients with concomitant unresectable cancer and acute cholecystitis is effective palliative short-term therapy by controlling infectious disease and maintaining quality of life. However, there are a few reports (9,11,13,14) of studies that evaluated the outcomes of long-term stent patency and adverse events in patients with acute cholecystitis who were contraindicated for cholecystectomy. Thus, in the present study, we evaluated the efficacy and safety of EGBS for patients with concomitant unresectable cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This complication is typically managed with cholecystectomy or placement of a cholecystostomy tube. Placement of transpapillary gallbladder stent (GBS) has been previously reported in patients with gallbladder cancer and acute cholecystitis [19][20][21][22][23][24]; however, not in the setting of bile duct stenting for distal biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the stent has remained in situ without any complications for 7 mo of follow-up in this case. Because the patency results of the endoscopic gallbladder stent placement vary [8,9] , regular evaluation of stent patency may be also required in this particular case.…”
Section: Introductionmentioning
confidence: 99%